QUALITY ASSESSMENT OF EXTENDED SHELF LIFE (ESL) MILK IN COMPARISON WITH OTHER KINDS OF PASTEURIZED MILK COMMERCIALLY AVAILABLE ON THE MARKET - NAYIL DINKÇI; ALEXANDRINA SIRBU (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry, 2024)
This research investigated milk commodities' physicochemical characteristics and sensory quality related to their processing techniques, namely ESL milk, compared to raw and pasteurized milk. Several chemical, physical, and sensory tests were carried out, and the obtained data were statistically evaluated. The results indicated that dry matter varied between 8.95 % and 13.11 %, while most milk samples contained more than 3.00 % fat. pH with values between 6.65 and 6.80 was consistent with titratable acidity results (0.135 % to 0.198 % lactic acid). The raw and ESL milk samples had positive lactoperoxidase results, while the pasteurized milk samples had negative lactoperoxidase results. The color analysis showed that the L values of the ESL milk samples were lower, and the color was darker than that of the pasteurized milk samples. The processing technology did not affect the samples' dry matter, fat content, and the a* and b* values but influenced the taste scores throughout the sensory analysis. While the scores for taste were statistically lower for ESL milk samples, the scores for odor and appearance were unaffected by the processing method. In conclusion, compared to pasteurized milk, ESL milk samples were not the first choice for the panelist's sensory scores.